Effectiveness and safety of add-on antidiabetic therapies to metformin in type 2 diabetes mellitus patients of south odisha population: A prospective observational cohort study. - Panda, Suvendu Kumar; Das, Bikas Chandra; Mishra, Pratyush; Panigrahy, Srikanta (Student's Journal of Health Research Africa, 2025)
Background Type 2 Diabetes Mellitus (T2DM) is a growing public health concern in India, particularly in resource-limited regions like South Odisha. While metformin remains the first-line therapy, combination regimens are often required for sustained glycemic control. However, real-world comparative data on the effectiveness and safety of such add-on therapies remain limited. Objective To assess the effectiveness and safety of various oral antidiabetic add-on regimens to metformin in T2DM patients attending a tertiary care center in South Odisha. Methods This prospective observational cohort study followed 289 patients (of 323 enrolled) over 9 months at MKCG Medical College, Berhampur. Patients were assessed at baseline, 3, 6, and 9 months for glycemic parameters, renal and lipid profiles, adverse drug reactions (ADRs), and health-related quality of life (HRQoL) using the WHO-5 Wellbeing Index.Statistical analysis was performed using SPSS v22.0 with significance set at p<0.05. Results The mean age of participants was 48.8 ± 15.5 years; 51% were male. Most were overweight or obese (66.7%) and 61.6% lived in rural areas. All add-on regimens showed significant reductions in FPG, PPPG, and HbA1c compared to metformin monotherapy (p < 0.05). DPP-4 inhibitor–based regimens (teneligliptin/vildagliptin) produced the greatest improvements in glycemic and lipid parameters (↓ triglycerides, LDL, VLDL; ↑ HDL). Renal and electrolyte values remained stable across groups. ADRs were reported in 157 patients, with hypoglycemia (19.7%) being most frequent, mainly linked to glimepiride. HRQoL scores improved significantly across all add-on groups compared to metformin alone. Conclusion Combination therapies, especially those including DPP-4 inhibitors, offer superior glycemic and lipid control with acceptable safety and improved quality of life in South Odisha T2DM patients. Recommendations Clinicians should consider DPP-4 inhibitor-based combinations for optimal outcomes in T2DM management. Further multicentre, randomized controlled trials with longer follow-up and inclusion of newer agents are recommended to strengthen the evidence base.